Prospective Clinical Study to Find out Epidemiology of Xerophthalmia in Children in a Tertiary Care Centre in India - Mishra, Deepak; Gulati, Megha; Bhushan, Prashant; Mohan, Nilesh; P, Bibhuti Sinha (International Journal of Clinical and Experimental Ophthalmology, 2017)
Objective: To study the epidemiology of xerophthalmia in children 2-6 years of age in North India. Methods: A prospective clinical study was done at two tertiary care centers of North India between 2010 to 2016, Cases were selected from routine OPD and children less than 6 years of age were examined by an ophthalmologist. Diagnosis and classification of Xerophthalmia was done according to WHO classification. All the data recording demographic profile, socioeconomic status, other health problems etc were recorded in a fixed proforma. Data was analyzed by SPSS version 16. Findings: Two thousand nine hundred forty six cases were included in the study after satisfying inclusion and exclusion criteria. The prevalence of night blindness was estimated to be 2.93% (95% Confidence Interval [CI]: 2.53-3.33) among children between 2 and 6 years of age. Xerophthalmia prevalence was 4.43% (95% CI: 4.19-4.67). Prevalence was more in girls than boys and higher in low socioeconomic status. Conclusion: Vitamin A deficiency is recognized to be a severe public health problem leading to corneal opacity and childhood blindness in most of the areas of North India